Oliver FOR YOUNG READERS : THE TRUE STORY OF A STOLEN DOG AND THE HUMANS HE BROUGHT TOGETHER - Carino, Steven J.; Tresniowski, Alex; Teplow, Rotem (Nashville, TN : Thomas Nelson, 2021)
"An inspirational true story about a dog and the community who saved him, Oliver for Young Readers by Steven Carino and Alex Tresniowski reminds kids that their own acts of kindness have the power to change lives"--
Ages 8-12.
Keywords: Lost dogs -- United States -- Anecdotes -- Juvenile literature; Dog owners -- United States -- Biography -- Juvenile literature; Human-animal -- Juvenile literature; Anecdotes; Biographies; Juvenile works